Lost cities - Morris, Neil, 1946- (North Mankato, MN : Smart Apple Media, 2008)
Photographs, maps, and illustrations describe the discovery of several lost cities including Pompeii, Troy, Machu Picchu, and Teotihuacan.
What is a lost city? -- Ur-the forgotten city -- Mohenjo-Daro -- Knossos -- Troy -- Pompeii -- Angkor -- Teotihuacan -- Great Zimbabwe -- El Dorado -- Tikal -- Machu Picchu -- Finding lost cities.
"A+".
Includes bibliographical references (p. 32) and index.
6.2
3-6
Keywords: Extinct cities -- Juvenile literature; Cities and towns, Ancient -- Juvenile literature; Excavations (Archaeology) -- Juvenile literature; Antiquities -- Juvenile literature; Civilization, Ancient -- Juvenile literature; Extinct cities; Cities and towns, Ancient; Excavations (Archaeology); Antiquities; Civilization, Ancient; Extinct cities; Ancient civilization; Archeology; Antiquities; Extinct cities; Cities and towns, Ancient; Excavations (Archaeology); Antiquities; Civilization, Ancient